Effectiveness of Acupressure KI3, SP 6, ST 36, ST 25 Against Weight Gain and Height in Stunting Toddlers 0-24 Months - Centis, Maria Conchita Leyla; Kusmiyati, Yuni; Suwondo, Ari; Herawati, Lucky; Hendriyani, Heni (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2025)
Stunting is a nutritional problem faced by the Indonesian state year after year. The impact of stunting is physical and intellectual. Various studies have been conducted to help overcome the problem of stunting, especially in height, weight, and motor development. One of these studies examined the effect of acupressure on changes in body weight and height in stunting children. This is a type of research: an Experimental design, a True experimental pre-posttest control-group design. The sampling technique used is simple random sampling, a sample of 30 children aged 0-2 years. The study found that the average body weight before acupressure was 9.6 kg, and after acupressure, it was 10.9 kg (p-value less than 0.05). The average height before the intervention was 73.6 cm, and after the intervention was 74.2 cm (p-value less than0.05). Acupressure affects weight gain and height.